Earned Value Concept as a Method to Analyze Cost and Time Control - Budi Suryo Utomo; Kartono Wibowo; Soedarsono S (Universitas Islam Sultan Agung, 2022)
The successful construction of infrastructure is dependent on many aspects, including at least time, cost, and control. With good control, deviations during the execution of work are expected to be minimized. In the case of the